2008
DOI: 10.1016/j.jmoneco.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Persistence in law of one price deviations: Evidence from micro-data

Abstract: We study the dynamics of good-by-good real exchange rates using a micro-panel of 270 goods prices drawn from major cities in 71 countries and 245 goods prices drawn from 13 major U.S. cities. We Þnd half-lives of deviations from the Law-of-One-Price for the average good is about 1 year; somewhat lower for U.S. cities and somewhat higher for cities in the OECD with LDC cities in between. This speed of adjustment is well below the concensus range of estimates of 3 to 5 years for purchasing power parity deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(188 citation statements)
references
References 43 publications
15
170
3
Order By: Relevance
“…However, the median value of the GMM median unbiased estimates was still below 1 year, 0.94 year, when we correct for the bias. 26 Our estimates are roughly consistent with the average half-life estimates from the micro-data evidence by Crucini and Shintani (2008) 27 and the differences of the point estimates for different countries are very similar to those of Murray and Papell (2002) for most countries. 28 J-test accepts our model specification for all countries with an exception of the UK.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, the median value of the GMM median unbiased estimates was still below 1 year, 0.94 year, when we correct for the bias. 26 Our estimates are roughly consistent with the average half-life estimates from the micro-data evidence by Crucini and Shintani (2008) 27 and the differences of the point estimates for different countries are very similar to those of Murray and Papell (2002) for most countries. 28 J-test accepts our model specification for all countries with an exception of the UK.…”
Section: Resultssupporting
confidence: 72%
“…While it is possible that the bias can solve the PPP puzzle under certain conditions, it is also possible that the bias is negligible under other conditions. For example, Chen and Engel (2005), Crucini and Shintani (2008), and Parsley and Wei (2007) have found negligible aggregation biases. Broda and Weinstein (2008) show that the aggregation bias of the form that Imbs, Mumtaz, Ravn, and Rey (2005) studied is small for their barcode data, even though the convergence coefficient rises as they move to aggregate indexes.…”
Section: Introductionmentioning
confidence: 99%
“…This high duration was described by Rogoff himself to be among one of the six major puzzles in international economics and has sparked a large body of literature. A number of studies have also shown that aggregation bias in both the time and product dimensions may help to reconcile this high duration of the adjustment process with faster convergence at the product and sectoral levels (Imbs et al, 2005;Crucini and Shintani, 2008;Bergin et al, 2013). The writings of Kilian and Zha (2002), Murray and Papell (2002), and Rossi (2005) have however questioned the existence of the puzzle given the large estimation uncertainty that emerges using both Bayesian and classical techniques.…”
Section: Atheoretical Benchmarksmentioning
confidence: 99%
“…As is evident in Table 5, the dispersion in price levels across locations is on the order of one-fourth to one-…fth as large as the mean level of dispersion at the level of individual goods and services. 9 Two obvious sources of variation that would average out across goods are measurement error and trade costs. Classical measurement error is, by de…nition, independently distributed across goods.…”
Section: Variance Decomposition Of Price Levelsmentioning
confidence: 99%